8-10 year-old fencers` aggression and response speed rating analysis - Biserova, G. K.; Gayfullina, N. G. (Theory and Practice of Physical Culture, 2020)
Results and conclusions. The simple sensorimotor response to personal aggression correlation analysis found a strong positive correlation of the personal aggression with the post-training bout simple sensorimotor response (r=0.48) and a weaker (trend-level) positive correlation with the pre-training bout simple sensorimotor response (r= 0.36). The fact that the pre- and post-training bout simple sensorimotor response rates are fairly close may be explained by the still poor age-specific behavioral self-controls in the beginner (first-year) fencers at the very start of the response speed training process. We also found that the clear correlation of the personal aggression and simple sensorimotor response tend to grow with the training bout experience - and this finding confirms our prior assumption on the natural aggression being of facilitative effect on the simple sensorimotor response progress in the beginner groups. Generally the higher is the natural aggression rate, the higher are the response rates in the beginner fencers.